Profil Kewirausahaan OPOP (One Pesantren One Product) dalam Meningkatkan Kesejahteraan Ekonomi Santri di Kabupaten Jombang, Jawa Timur - Sucipto , Sucipto; Fatmasari , Rhini; Jaya, Fitra (Politeknik Ganesha Medan, 2024)
One Islamic Boarding School (Pesantren) One Product (OPOP) program aims to create independence for the people through students, the community and Islamic boarding schools, so that they are able to be independent economically, socially and also to encourage skills development, production technology, distribution, marketing through an innovative and strategic approach. As for the aim of this research is to determine the variables that influence the objectives of One Pesantren One Product (OPOP) program run by the Islamic Boarding School in improving the welfare of students through a quantitative approach. The sample in this study consisted of 40 respondents from three Islamic boarding schools. The research results show that santripreneurs, pesantrenpreneurs and sociopreneurs influence the objectives of One Islamic Boarding School One Product (OPOP) program. The results of surveys and interviews in the field show that the selection of Islamic boarding schools involved in the OPOP program was carried out through selection. The instillation of santripreneur values is formed through intense, routine and systematic education and training, while pesantrenpreneur is implemented through extracurricular and intracurricular activities.